1992
DOI: 10.1016/0014-5793(92)81319-h
|View full text |Cite
|
Sign up to set email alerts
|

A new crystal form of the complex between seryl‐tRNA synthetase and tRNASer from Thermus thermophilus that diffracts to 2.8 Å resolution

Abstract: A new crystal form of the complex between seryl-tRNA synthetase and tRNASer from Thermus thermophilus that diffracts to 2.8 A resolution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Form four crystals of the Tthermophilus SerRS-tRNASer (GGA) complex were grown as described (Yaremchuk et al, 1992) but in the presence of 300 jM (5'-O-[N-(L-seryl)-sulfamoyl]adenosine} a synthetic analogue of seryl-adenylate (Belrhali et al, 1994). These crystals contain a single tRNA molecule bound to the SerRS dimer in the crystal asymmetric unit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Form four crystals of the Tthermophilus SerRS-tRNASer (GGA) complex were grown as described (Yaremchuk et al, 1992) but in the presence of 300 jM (5'-O-[N-(L-seryl)-sulfamoyl]adenosine} a synthetic analogue of seryl-adenylate (Belrhali et al, 1994). These crystals contain a single tRNA molecule bound to the SerRS dimer in the crystal asymmetric unit.…”
Section: Methodsmentioning
confidence: 99%
“…Here we present an improved structure in which the interactions of the acceptor stem with the synthetase are now visible, even though bases 74-76 at the extreme 3' end of the tRNA remain poorly ordered. Data has been remeasured on the same crystal form as that previously described (Yaremchuk et al, 1992;Biou et al, 1994) which contains a single tRNA bound to the SerRS dimer. However, there are two significant differences: firstly, the complex was cocrystallized in the presence of the sulfamoyl analogue of the natural intermediate seryl-adenylate (Ser-AMS, Belrhali et al 1994) and secondly, data collection was performed on frozen crystals at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Arginine 94 is located in the loop between helix H2 and ␤-strand A4 and according to the docking model positioned to interact with the T-loop of the tRNA Ser . The crystal structure of the SerRS⅐tRNA Ser complex from T. thermophilus (23,26,46) revealed that the tRNA-binding coiled-coil of bacterial SerRS is buried between the TC arm and the long extra arm of tRNA Ser . Likewise, biochemical studies on the mammalian mitochondrial system pointed to the importance of the T-loop, which is the main identity element for two unusual tRNA Ser isoacceptors.…”
Section: Identification Of Amino Acids In the N-terminal Domain Of MMmentioning
confidence: 99%
“…When the saturation-binding data from Figure 3a was fit to the Hill equation (Figure 3b) the Hill coefficients in the absence and the presence of the MtArgRS were calculated (Table 3). The observed cooperativity for binding of tRNA Ser to SerRS (Figure 3a) is also reflected in the Hill coefficient, which for MtSerRS:tRNA Ser (Table 3) 11,30 and biochemical studies on heterodimers. 12,32 SerRS from the yeast Saccharomyces cerevisiae has also been found to bind one or two tRNA Ser cooperatively 24 .…”
Section: Alteration Of K D Value In Mtserrs:trna Ser Association Uponmentioning
confidence: 86%